2000
DOI: 10.4049/jimmunol.165.9.5338
|View full text |Cite
|
Sign up to set email alerts
|

Human Double-Negative T Cells in Systemic Lupus Erythematosus Provide Help for IgG and Are Restricted by CD1c

Abstract: To understand the mechanism of T cell help for IgG production in systemic lupus erythematosus (SLE) we investigated the response of CD4- and CD8-negative (double-negative (DN)) T cells because 1) DN T cells are present at unusually high frequency in patients with SLE and can induce pathogenic autoantibodies; 2) the DN T cell repertoire includes cells restricted by CD1 Ag-presenting molecules; and 3) CD1c is expressed on a population of circulating B cells. We derived DN T cell lines from SLE patients and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 55 publications
7
79
0
Order By: Relevance
“…Such findings are in keeping with previous reports (56,57) and, more generally, with helper activity by CD1-restricted T cells (58). The contribution of PL-specific T cells to allergic reactions in the lung of pollen-sensitive patients is not demonstrable with in vitro experiments, and therefore we can only speculate about their role in the pathogenesis of this disease.…”
Section: Articlesupporting
confidence: 92%
“…Such findings are in keeping with previous reports (56,57) and, more generally, with helper activity by CD1-restricted T cells (58). The contribution of PL-specific T cells to allergic reactions in the lung of pollen-sensitive patients is not demonstrable with in vitro experiments, and therefore we can only speculate about their role in the pathogenesis of this disease.…”
Section: Articlesupporting
confidence: 92%
“…Several lines of evidence suggest a role for CD1c and CD1c self-reactive T cells in human autoinflammatory and autoimmune diseases. For example, CD1c self-reactive T cells were found to be elevated in autoimmune thyroid tissues and in systemic lupus erythematosus (SLE) (23,24). In SLE, these cells induce Ig class switching to IgG and increase Ig secretion in CD1c+ B cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CD1c self-reactive T cells were found to be elevated in autoimmune thyroid tissues and in systemic lupus erythematosus (SLE) (23,24). In SLE, these cells induce Ig class switching to IgG and increase Ig secretion in CD1c+ B cells (24). Conversely, CD1c high myeloid dendritic cells (CD1c+mDC) infiltrate inflamed tissues in different autoimmune conditions, including, for example, rheumatoid arthritis (RA), vitiligo, or autoimmune thyroiditis (23,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Goodrum et al [88] used whole peripheral blood monocytes from freshly donated normal human blood, with which it was shown that CD4 single positive T cells proliferated strongest, Sieling et al [90] reported that CD4/CD8 double negative T cells from auto-immune systemic lupus erythematosus (SLE) patients induced antibody isotype switching from IgM to IgG in a anti-cholesterol antibody activity in TB patient sera. How this may relate to the establishment of TB is discussed in more detail below.…”
Section: Does Structure Matter?mentioning
confidence: 99%